Streptococcus mutans extracellular DNA is upregulated during growth in biofilms, actively released via membrane vesicles, and influenced by components of the protein secretion machinery - Liao, Sumei; Klein, Marlise I. [UNESP]; Heim, Kyle P.; Fan, Yuwei; Bitoun, Jacob P.; Ahn, San-Joon; Burne, Robert A.; Koo, Hyun; Brady, L. Jeannine; Wen, Zezhang T. (American Society for Microbiology, 2014)
Streptococcus mutans, a major etiological agent of human dental caries, lives primarily on the tooth surface in biofilms. Limited information is available concerning the extracellular DNA (eDNA) as a scaffolding matrix in S. mutans biofilms. This study demonstrates that S. mutans produces eDNA by multiple avenues, including lysis-independent membrane vesicles. Unlike eDNAs from cell lysis that were abundant and mainly concentrated around broken cells or cell debris with floating open ends, eDNAs produced via the lysis-independent pathway appeared scattered but in a structured network under scanning electron microscopy. Compared to eDNA production of planktonic cultures, eDNA production in 5- and 24-h biofilms was increased by >3- and >1.6-fold, respectively. The addition of DNase I to growth medium significantly reduced biofilm formation. In an in vitro adherence assay, added chromosomal DNA alone had a limited effect on S. mutans adherence to saliva-coated hydroxylapatite beads, but in conjunction with glucans synthesized using purified glucosyltransferase B, the adherence was significantly enhanced. Deletion of sortase A, the transpeptidase that covalently couples multiple surface-associated proteins to the cell wall peptidoglycan, significantly reduced eDNA in both planktonic and biofilm cultures. Sortase A deficiency did not have a significant effect on membrane vesicle production; however, the protein profile of the mutant membrane vesicles was significantly altered, including reduction of adhesin P1 and glucan-binding proteins B and C. Relative to the wild type, deficiency of protein secretion and membrane protein insertion machinery components, including Ffh, YidC1, and YidC2, also caused significant reductions in eDNA. © 2014, American Society for Microbiology.